Changes of parvalbumin expression in the spinal cord after peripheral inflammation - Zachařová, Gisela; Sojka, David; Paleček, Jiří (Physiological research, 2009)
Parvalbumin (PV) is a calcium-binding protein that is expressed by numerous neuronal subpopulations in the central nervous system. Staining for PV was often used in neuroanatomical studies in the past. Recently, several studies have suggested that PV acts in neurons as a mobile endogenous calcium buffer that affects temporo-spatial characteristics of calcium transients and is involved in modulation of synaptic transmission. In our experiments, expression of PV in the lumbar dorsal horn spinal cord was evaluated using densitometric analysis of immunohistological sections and Western-blot techniques in control and arthritic rats. There was a significant reduction of PV immunoreactivity in the superficial dorsal horn region ipsilateral to the arthritis after induction of the peripheral inflammation. The ipsilateral area and intensity of PV staining in this area were reduced to 38 % and 37 %, respectively, out of the total PV staining on both sides. It is suggested that this reduction may reflect decreased expression of PV in GABAergic inhibitory neurons. Reduction of PV concentration in the presynaptic GABAergic terminals could lead to potentiation of inhibitory transmission in the spinal cord. Our results suggest that changes in expression of calcium-binding proteins in spinal cord dorsal horn neurons may modulate nociceptive transmission.
Keywords: Animals; Parvalbumins; potkani Wistar; Kaolin; financování organizované; zvířata; lumbosakrální krajina; kaolin; parvalbuminy; down regulace; Lumbosacral Region; Financing, Organized; karagenan; Down-Regulation; Rats; Posterior Horn Cells; Male; Rats, Wistar; buňky zadních rohů míšních; Arthritis, Experimental; krysa rodu Rattus; Carrageenan; artritida experimentální; mužské pohlaví